2006
DOI: 10.1007/s00429-006-0094-0
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-based contraction is not necessary for cardiac c-looping in the chick embryo

Abstract: During the initial phase of cardiac looping, known as c-looping, the heart bends and twists into a c-shaped tube with the convex outer curvature normally directed toward the right side of the embryo. Despite intensive study for more than 80 years, the biophysical mechanisms that drive and regulate looping remain poorly understood, although some investigators have speculated that differential cytoskeletal contraction supplies the driving force for c-looping. The purpose of this investigation was to test this hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 44 publications
11
38
0
Order By: Relevance
“…The first observation is consistent with recent evidence showing that c-looping does not require contraction (Rémond et al, 2006). Recently, Latacha et al (2005) suggested that actin polymerization drives the bending component of c-looping.…”
Section: Increased Heart Stiffness Is Caused By Cytoskeletal Contractionsupporting
confidence: 87%
See 2 more Smart Citations
“…The first observation is consistent with recent evidence showing that c-looping does not require contraction (Rémond et al, 2006). Recently, Latacha et al (2005) suggested that actin polymerization drives the bending component of c-looping.…”
Section: Increased Heart Stiffness Is Caused By Cytoskeletal Contractionsupporting
confidence: 87%
“…In embryos cultured with the SPL intact, looping was unaffected by exposure to the drug (Fig. 5A-C), corroborating recent evidence from our laboratory that nonmuscle myosin II is not necessary for normal c-looping (Rémond et al, 2006). In hearts where the SPL was removed, however, exposure to Y-27632 resulted in ventral (and some rightward) bending, but little or no rotation (Fig.…”
Section: Asymmetric Cytoskeletal Contraction Drives Delayed Cardiac Tsupporting
confidence: 87%
See 1 more Smart Citation
“…They concluded, however, that the observed heart and foregut defects were not due to a lack of contractility, as treatment with the myosin light chain kinase (MLCK) inhibitor ML-9 did not reproduce the observed abnormalities. Previous work in our laboratory, however, has shown that the similar but more specific MLCK inhibitor ML-7 (Bain et al, 2003) did not significantly reduce either myosin regulatory light chain phosphorylation or tissue stiffness in looping chick hearts (Rémond et al, 2006). It is thus possible that ML-9 did not completely suppress cytoskeletal contraction, and that cardia bifida produced by treatment with Y27632 was (at least in part) due to attenuated contraction.…”
mentioning
confidence: 81%
“…Moreover, the disruption of myosin-based tension generation with a ROCK inhibitor during the initial stages of heart looping disturbs morphogenesis in this system (Wei et al, 2002); however, tension inhibitors do not interfere with heart looping in chicks, so the conservation of this mechanism remains uncertain (Remond et al, 2006). In rats, the heart also alters its stiffness according to its developmental stage by changing the isoform ratios of the cytoskeletal protein titin, the elastic properties of which influence the physical compliance of heart tissue (Lahmers et al, 2004).…”
Section: Organogenesismentioning
confidence: 99%